The Correlation Of Body Mass Index And Age With Disability Rate In Patients With Grade Ii-Iv Knee Osteoarthritis According To Kellgren-Lawrence At Rs Phc Surabaya - Khudrati, Wilson Christianto; Handoyo, Henry Ricardo; Nugroho, Nunung (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction: Knee osteoarthritis is a degenerative joint disease that is most common in adults and the elderly in many countries. Incidence of osteoarthritis is increased steadily over the last 15 years. Currently, there is still no simple therapy to cure osteoarthritis disease. Therefore, it is very important to find the risk factor of osteoarthritis to do etiology prevention. Aim: The purpose of this study is to discover the correlation of body mass index and age with disability rate in patients with Grade II-IV Knee Osteoarthritis. Methods: This research is an observational analytical study using cross sectional approach. The sampling techniques used was purposive sampling. Data collection was done by interviewing respondents using KOOS-PS questionnaire. Result: There is a significant, strong correlation between body mass index and disability rate in patients with knee joint OA (r=0.661). However, there is no significant correlation between age and knee joint OA disability (r=0.150). A moderate correlation is found, respectively, between body mass index and the grade of knee joint OA (r=0.424) and also between age and the grade of knee joint OA (r=0.352). Conclusion: There is a significant correlation between body mass index and disability rate of patients with knee joint OA.